2011
DOI: 10.1002/hed.21823
|View full text |Cite
|
Sign up to set email alerts
|

Observer variation in the histopathologic assessment of extranodal tumor spread in lymph node metastases in the neck

Abstract: The intraobserver and interobserver agreement among pathologists in the assessment of the presence of ENS was low in metastatic lymph nodes in the neck. Because of the widely accepted prognostic significance and therapeutic consequences of ENS, there is a need for internationally accepted reproducible criterion for the histopathologic assessment of ENS in metastatic lymph nodes in the neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 37 publications
0
42
0
2
Order By: Relevance
“…For instance, in a study by Shah et al in oral cavity cancer, ''soft tissue involvement'' was reported in 69 of 704 (10%) patients, separate from ECS but there were no defined criteria for ''soft tissue involvement.'' [22] Due to potential prognostic and therapeutic implications, this underscores the importance of using specific criteria, standard assessment, and standard reporting of STM in p16+ OPSCC, similar to ECS [23,24].…”
Section: Discussionmentioning
confidence: 98%
“…For instance, in a study by Shah et al in oral cavity cancer, ''soft tissue involvement'' was reported in 69 of 704 (10%) patients, separate from ECS but there were no defined criteria for ''soft tissue involvement.'' [22] Due to potential prognostic and therapeutic implications, this underscores the importance of using specific criteria, standard assessment, and standard reporting of STM in p16+ OPSCC, similar to ECS [23,24].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we recently performed a study 7 to examine the level of agreement among pathologists on the presence or absence of ECS. The interobserver and intraobserver agreement among 10 pathologists on the diagnosis of ECS in 41 tumor-positive lymph nodes was evaluated.…”
Section: To the Editormentioning
confidence: 99%
“…Although diagnostic debate is obviously minimal in cases where the invasive front of the metastatic deposit is located away from the lymph node capsule (either overtly confined to the lymph node or extending overtly outside of the lymph node), a worrisome degree of intra-and interobserver variability obscures the diagnostic assessment of ECS in many other instances. 7 This is most pronounced when the invasive tumor front of the metastatic deposit is located in close approximation to the capsule of the metastatic lymph node, in cases in which the invasive tumor front is located in or near the nodal hilum area (which lacks a capsule), in cases where the capsule is discontinuous, in cases where a desmoplastic immune response surrounds and mimics the capsule, or in cases where capsular breach is incomplete. In these cases, uncertainty regarding the presence or absence of ECS may induce a degree of overdiagnosis fuelled by the possibility of adverse prognostic implications derived from a missed ECS diagnosis.…”
Section: Extracapsular Nodal Spreadmentioning
confidence: 99%